2014
DOI: 10.1158/1535-7163.mct-14-0172
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of OSU-03012 Toxicity by ER Stress Proteins and ER Stress–Inducing Drugs

Abstract: The present studies examined the toxic interaction between the non-coxib celecoxib derivative OSU-03012 and phosphodiesterase 5 (PDE5) inhibitors, and to determine the roles of endoplasmic reticulum stress response regulators in cell survival. PDE5 inhibitors interacted in a greater than additive fashion with OSU-03012 to kill parental glioma and stem-like glioma cells. Knock down of the endoplasmic reticulum stress response proteins IRE1 or XBP1 enhanced the lethality of OSU-03012, and of [OSU-03012 + PDE5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 56 publications
2
61
1
Order By: Relevance
“…Sildenafil and celecoxib treatment also inhibited the growth of mammary tumors in vivo which was enhanced by the multiple sclerosis drug FTY720 (Fingolimod, Gilenya) that is known to suppress sphingosine-1-phosphate (S1P) signaling through S1P production and increasing the ceramide levels (Booth et al, 2014c). Sildenafil and tadalafil were also shown to interact with non-coxib celecoxib derivative OSU-03012 (lacking COX2-inhibitory activity) in killing of glioblastoma multiforme (GBM) cells by recruiting death receptor signaling (Booth et al, 2014b). …”
Section: Pde5 Inhibitors In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Sildenafil and celecoxib treatment also inhibited the growth of mammary tumors in vivo which was enhanced by the multiple sclerosis drug FTY720 (Fingolimod, Gilenya) that is known to suppress sphingosine-1-phosphate (S1P) signaling through S1P production and increasing the ceramide levels (Booth et al, 2014c). Sildenafil and tadalafil were also shown to interact with non-coxib celecoxib derivative OSU-03012 (lacking COX2-inhibitory activity) in killing of glioblastoma multiforme (GBM) cells by recruiting death receptor signaling (Booth et al, 2014b). …”
Section: Pde5 Inhibitors In Cancermentioning
confidence: 99%
“…In recent years, there has been tremendous interest in identifying new clinical uses of PDE5 inhibitors in various ailments including cardiovascular disease (Kukreja et al, 2004; Kukreja et al, 2005; Kukreja et al, 2011), diabetes (Giannetta et al, 2012; Koka et al, 2012; Koka et al, 2013; Koka et al, 2014; Varma et al, 2012) and cancer (Black et al, 2008; Booth et al, 2014a; Booth et al, 2014c; Booth et al, 2014b; Das et al, 2010; Hamilton et al, 2013; Resnick et al, 2009; Roberts et al, 2014). Today, close to 100 clinical trials (http://www.clinicaltrials.gov) with PDE5 inhibitors focusing on the potential cardiovascular benefits have been completed or are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Although activation of the death receptor CD95 could play a role in the drug interactions, other data argued that prolonged high levels of autophagosome formation also were essential for the lethal synergistic combination effects with the PDE5 inhibitor [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies then linked the effects of AR-12 on tumor cell biology to the regulation of chaperone proteins [4, 5]. In more recent studies, we have shown that sorafenib, pazopanib, AR-12 and regorafenib can reduce the apparent expression chaperone proteins HSP90, GRP78 and HSP70 using an in-cell western/immuno-fluorescence approach [512].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphodiesterase 5 inhibitors including sildenafil (Viagra) and tadalafil (Cialis) were shown to interact with OSU-03012 to facilitate killing in a wide variety of tumor cells. The enhanced killing effect of the drug combination was associated with enhanced PERK-dependent ER stress signaling and autophagosome formation, as well as through death receptor activation [6]. Congruent data were obtained using the parent drug of OSU-03012, celecoxib, and also with the multi-kinase inhibitors sorafenib, regorafenib and pazopanib [7,8].…”
Section: Commentarymentioning
confidence: 99%